Pembelajaran Penanganan dan Perawatan Cedera (PPC) Berbasis Ramuan Herbal Tradisional Mbojo “Lo’i Pa’i Piri” untuk Mahasiswa - Fauqi, Amal; Susila, Linda (JUPE : Jurnal Pendidikan Mandala, 2023)
The problems encountered by researchers as lecturers in Injury Handling and Care (PPC) courses include: (a) Injuries that they study and understand are identical Handling and treatment must be handled in a hospital using prescription drugs from an injury specialist (b) Background students' understanding of medicinal plants and the composition of traditional herbal medicines is still minimal (c) Student knowledge is still limited in understanding the purpose and benefits of consuming Mbojo traditional herbal ingredients “Lo'i Pa'i Piri”. The problem solving model in this research uses Hellison's model which has been tested for its validity, practicality, and effectiveness. This study uses a 4-D development model (Define, Design, Develop, and Disseminate. In conclusion, teaching materials for Handling and Treatment of Injury Using Mbojo's Traditional Herbal Concoction "Loi Pai Piri" are sourced from plants and plants of the Bima Community with the Hellison'S model approach. good category, because all the learning tools in the teaching materials are valid based on expert judgment, student responses are very positive because of their practicality when used in learning, and can improve students' critical thinking skills.